Clinicopathological parallelism in placental microbial colonization - T. Yu. Marochko; L. A. Levanova; N. B. Kolesnikova; M. N. Surina; O. B. Karelina; K. R. Kopytova (Фундаментальная и клиническая медицина)
Aim. To study the course of pregnancy, childbirth and the postpartum period in pregnant women with placental microbial colonization; to investigate placental morphology during the microbial colonization.Materials and Methods. We retrospectively investigated 128 case histories of the pregnant women with or without (n = 64) placental microbial colonization.Results. Enterobacteriaceae spp., Enterococcaceae spp. and Staphylococcaceae spp. were respectively isolated from placentas of 24 (37.5%), 19 (29.7%), and 19 (29.7%) women with placental microbial colonization. Candida albicans was isolated in 2 (3.1%) cases. All placentas excised from women without placental microbial colonization were sterile. Vaginal delivery occurred in 61 (95.3%) women with placental microbial colonization but only in 24 (37.5%) women without (p = 0.001). Subinvolution was revealed in 10 (15.6%) and 4 (6.3%) (р = 0.09), lochiometra was found in 4 (6.3%) and 2 (3.1%) (р = 0.409), and wound infections were observed in 5 (7.8%) and 1 (1.6%) (p = 0.095) women with or without placental microbial colonization, respectively. Therefore, prevalence of postpartum complications did not differ significantly between the groups. Placental inflammation was detected in 27(42.2%) and 14 (21.9%) (p = 0.014) patients with or without placental microbial colonization, respectively.Conclusions. Placental inflammation is associated with microbial colonization which is more common in women who undergo vaginal delivery.